Expressão do transportador de glicose GLUT3 e atividade da acetilcolinesterase em cérebro de ratos adultos submetidos à desnutrição no início da vida - Vasconcelos, Vívian Sarmento de (2009)
The protein-energy malnutrition is one of the most serious nutritional problems that occur in developing countries. The energy and nutritional deficiency in early life can cause significant changes in different stages of development of central nervous system, since the cases of hyperplasia, hypertrophy and myelinization occur in more intense. The brain uses glucose as its main energy substrate. However, under certain physiological conditions, as during the weaning or during prolonged fasting, the cells may use other substrates in order to meet their metabolic needs. The transport of glucose to the nerve cells requires the presence of specific transporter proteins called GLUT s (Glucose Transporters) to perform the transport of glucose by facilitated diffusion. Besides the transporters of glucose, transporter proteins of monocarboxilatos (MCTs) are responsible for neuronal influx of lactate, MCT1 being the main responsible for providing energy to neurons during maturation of nervous tissue. The acetylcholine is a major neurotransmitter of the nervous system and is associated with the maintenance processes of attention, learning and memory. In the synaptic cleft acetylcholine is degraded by the enzyme cholinesterase, the acetylcholinesterase (AChE) and the butyrilcholinesterase (BuChE). Increased activity of fractions of AChE has been associated with states of dementia in elderly patients and the loss of cognitive function in patients with Alzheimer's Disease. This work is proposed to study the expression of neuronal glucose transporter GLUT3 and activity of the enzyme acetylcholinesterase (AChE) in brain of young adult rats (84 days of life) who were breastfed in litters formed by 6 (control group) or 12 pups (undernourished group). The results showed that the weight of the brains of malnourished rats was significantly lower (P <0001, Student s t test) compared to controls. The blood glucose levels and the expression of GLUT3 in total cortical membranes was also reduced by malnutrition (P <0001, Student s t test). The activity of AChE in different brain homogenate showed a significant interaction (P = 0019, two-way ANOVA, Tukey s test) between nutritional status and the type of fraction of the homogenate, with a significant reduction (p< 0,05) in activity this enzyme in the brain homogenate in control group. These results show for the first time that malnutrition during the period of weaning reduces the expression of GLUT3 and vi that the increased activity of acetylcholinesterase associated with decreased in the expression of the main glucose transporter in the brain could contribute to cognitive deficits and changes in brain metabolic activity.